Nutritional status among children aged one to six years in tribal area - Reddy, Palle Lokhnath; Anand Chand, Aluka (International Journal Of Community Medicine And Public Health, 2020)
Background: Nutrition in children is considered as a major concern for good health and also for normal growth and development. The present study aimed to estimate the prevalence of malnutrition in 1 to 6 years children. Methods: This was a community based cross sectional carried out in a south Indian tribal area for a period of 5 years among 1020 children. The anthropometric measurements categorization among children was done using world health organization (WHO) guidelines. Data was analyzed using microsoft excel 2010. Results: Out of 1020 children, nutritional status based on underweight, stunting and wasting was 30.80%, 26.8% and 15.68% respectively. Severe degree of underweight, stunting and wasting was observed in 76.4%, 64.7% and 5.49% respectively. Conclusions: Under nutrition was significantly high in infants and it decreased with increasing in age and significantly higher number of female children were stunted and underweight compared to male children.